Kompleksitas Rezim di Uni Eropa: Upaya Penanganan Pengungsi dan Pencari Suaka - Lunyka Adelina Pertiwi (Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
This paper discusses regime complexity in European Union regarding its eﬀorts to handle the inﬂux of refugees and asylum seekers. By using qualitative method, this paper explains to what extent of regime complexity in European Union and how Germany, as a superpower in European Union, parse the complexity. An analysing process applies concepts of regime complexity and strategic inconsistency. The paperconcludes that German try to parse the regimes network in European Union which is very complex and overlapping through strategic inconsistency, namely changing and maximizing its goods and externalities, and individual situation, soEuropean Union successfully reduce the inﬂux of refugees and asylum seekers and implement burden-share.